Microenvironmental pH-modification to improve dissolution behavior and oral absorption for drugs with pH-dependent solubility. (April 2014) - Taniguchi, Chika; Kawabata, Yohei; Wada, Koichi; Yamada, Shizuo; Onoue, Satomi
<x xml:space="preserve">Abstract</x> Introduction: Drug release and oral absorption of drugs with pH-dependent solubility are influenced by the conditions in the gastrointestinal tract. In some cases, poor oral absorption has been observed for these drugs, causing insufficient drug efficacy. The pH-modification of a formulation could be a promising approach to overcome the poor oral absorption of drugs with pH-dependent solubility. Areas covered: The present review aims to summarize the pH-modifier approach and strategic analyses of microenvironmental pH for formulation design and development. We also provide literature- and patent-based examples of the application of pH-modification technology to solid dosage forms. Expert opinion: For the pH-modification approach, the microenvironmental pH at the diffusion area can be altered by dissolving pH-modifying excipients in the formulation. The modulation of the microenvironmental pH could improve dissolution behavior of drugs with pH-dependent solubility, possibly leading to better oral absorption. According to this concept, the modulated level of microenvironmental pH and its duration can be key factors for improvement in drug dissolution. The measurement of microenvironmental pH and release of pH-modifier would provide theoretical insight for the selection of an appropriate pH-modifier and optimization of the formulation.